Topology optimization of a 120° bending high temperature superconducting photonic crystal waveguide - Fei Wang; Gang Liu; Yongpan Gao; Shuzhen Lu; Baonan Jia; Xiaoning Guan; Lihong Han; Pengfei Lu (Results in Physics, 2024)
The two-dimensional high-temperature superconducting photonic crystal structure has been widely studied as a novel type of photonic crystal structure. This paper investigates the transmission characteristics of a superconducting photonic crystal waveguide with a 120° bending triangular lattice arrangement in the mid-infrared wavelength range. Through the topology optimization methods, we have achieved enhanced transmittance contrast and widened transmission bandwidth of this waveguide. Our research provides parameter and method support for high-performance photonic crystal integrated devices.